Effect of shrimp farming on nitrogen levels in the waters of Kandaleru creek, Andhra Pradesh - Joseph, K O; Gupta, B P; Arasu, A R T (Indian Journal of Fisheries, 2011)
Shrimp farming is a rapidly growing and economically attractive industry in many tropical nations. In India, many shrimp farms mushroomed haphazardly all along the coast. Production of shrimp is often limited by deterioration of water quality, as discharge from aquafarms ultimately reach the receiving waters such as rivers, creeks, estuaries and sea or land. Shrimp farms are generally developed in groups and in certain locations the inlet from one farm receives water from the outlet of nearby farm. When compared to other industries, pollution from aquaculture is negligible and its source is the nitrogenous excretory wastes of the cultured organisms, which may cause eutrophication in marine/estuarine systems. A case study was undertaken in Kandaleru creek area in Nellore District of Andhra Pradesh in order to assess the nutrient release in terms of nitrogen, due to large scale shrimp farming and its impact on the creek evaluated. The changes in nitrogen levels are quite high and show a marked risk of eutrophication in the creek when semi-intensive shrimp farming is practiced in the area.